2021
DOI: 10.1021/acsnano.1c00955
|View full text |Cite
|
Sign up to set email alerts
|

Armored Droplets as Soft Nanocarriers for Encapsulation and Release under Flow Conditions

Abstract: Technical challenges in precision medicine and environmental remediation create an increasing demand for smart materials that can select and deliver a probe load to targets with high precision. In this context, soft nanomaterials have attracted considerable attention due to their ability to simultaneously adapt their morphology and functionality to complex ambients. Two major challenges are to precisely control this adaptability under dynamic conditions and provide predesigned functionalities that can be manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Despite the aforementioned progress achieved in the leading materials with the solid form, the behaviors of liquid nanodroplets at different interfaces have been relatively less reported and understood. Unraveling the fundamental physicochemical processes of interfacial liquid droplets offer unique and promising applications in the elds including nanoreactors 12 , micro uidics 13 , nanomotors 14 , nanotransporters 15 , 3D additive manufacturing 16 , nanowelding 17 , nanowetting 18 , spraying 19 , and exible/wearable devices 20 . It has been shown that the motion velocities of water microdroplets are increased dramatically on the superhydrophobic interfaces 21 , and the chemical reactions can be also facilitated on the surface of liquid droplets 22 as well as the solid-liquid interfaces 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned progress achieved in the leading materials with the solid form, the behaviors of liquid nanodroplets at different interfaces have been relatively less reported and understood. Unraveling the fundamental physicochemical processes of interfacial liquid droplets offer unique and promising applications in the elds including nanoreactors 12 , micro uidics 13 , nanomotors 14 , nanotransporters 15 , 3D additive manufacturing 16 , nanowelding 17 , nanowetting 18 , spraying 19 , and exible/wearable devices 20 . It has been shown that the motion velocities of water microdroplets are increased dramatically on the superhydrophobic interfaces 21 , and the chemical reactions can be also facilitated on the surface of liquid droplets 22 as well as the solid-liquid interfaces 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…A dissipative particle dynamics (DPD) simulation [1,2] method is a type of coarsegrained molecular simulation method, which has proven to be a powerful tool for investigating fluid events occurring on a wide range of spatio-temporal scales compared to all-atom simulations. Using DPD method, many studies have been conducted for both the statics and dynamics of complex system at the mesoscopic level, such as unique self-assembled structures formed by nanoparticles or polymers [3][4][5][6], mechanical or rheological properties of soft materials [7][8][9], medical materials and biological functions [10][11][12][13], and so forth. Huang et al [4] proposed a method to fabricate various two-dimensional nanostructures using selfassembly of block copolymers and demonstrated it in DPD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, DPD simulations were performed to understand how SWCNTs improve the mechanical properties of the fibers at a molecular level. Sicard and Toro-Mendoza [13] reported on the computational design of soft nanocarriers using pickering emulsions (nanoparticle armored droplet), able to selectively encapsulate or release a probe load under specific flow conditions. They described in detail the mechanisms at play in the formation of pocket-like structures and their stability under external flow.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the porosity has been described to depend on the size, shape and number of particles covering the interface, [19,20] affinity characteristics correspond to the surface chemistry of the material. [21] Additionally, the ability to release cargo under pre-determined stimuli is a key feature in, for example, drug delivery systems [22] or, if several uptake-release cycles are successfully achieved, a reusable and sustainable removal of contaminants from waste water. Therefore, PEs show an enormous potential to contribute to the United Nations Sustainable Development Goal #6 -Clean Water and Sanitation.Important design parameters that control the formation, stability and properties of PEs are: 1) the water phase conditions, including pH and ionic strength; 2) the oil phase conditions, particularly, the oil polarity; 3) the oil-water ratio; 4) the amount, aspect ratio, surface chemistry, and roughness of the (nano)particles; and 5) the emulsification process (e.g., sonication versus microfluidic techniques).…”
mentioning
confidence: 99%
“…Whereas the porosity has been described to depend on the size, shape and number of particles covering the interface, [19,20] affinity characteristics correspond to the surface chemistry of the material. [21] Additionally, the ability to release cargo under pre-determined stimuli is a key feature in, for example, drug delivery systems [22] or, if several uptake-release cycles are successfully achieved, a reusable and sustainable removal of contaminants from waste water. Therefore, PEs show an enormous potential to contribute to the United Nations Sustainable Development Goal #6 -Clean Water and Sanitation.…”
mentioning
confidence: 99%